Institutional competition, political process and holdup - Bruno Deffains; Dominique M. Demougin (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
We compare the effect of legal and institutional competition for the design of labor institutions in an environment characterized by holdup problems in human and physical capital. We compare autarky with the two country case, assuming that capital is perfectly mobile and labor immobile. We distinguish two cases. In the first, the political system is free from capture, while in the second, we examine the case where labor captures the institutional design problem. We find that in the former case, a competition of systems reduces welfare while in the latter it improves the overall outcome.
Keywords: 330